Democratic Movements and Challenges in Nepal - Ghimire, Tara Nath (Humanities and Social Sciences Journal, 2022)
This article examines and analyses the democratic movements and challenges in Nepal. Democratic system of government is considered one of the best and most superlative governing systems of countries in the world. In the history of civilization, democracy has been fundamental in transforming the globe from monarchy, imperialism and invasion to constitutional democracy, self-determination, mutual understanding and peaceful co-existence. The democratic system is preferable and a better governing system because of the participation of people in decision-making. There have been many movements for the establishment of democracy in the world and those movements have contributed significantly not only democracy but also equally to human rights. Also in Nepal, there have been several movements for the establishment of the democratic system. For a long time, Nepal had a unitary system with absolute monarchy. A federal republic system has been established in Nepal through a long and continuous struggle involving various political movements. This study is related to those movements that have some significant role in the establishment of democracy in Nepal along with their challenges. It is qualitative research in nature and used only secondary data. The secondary data and facts have been drawn from library and related reviews and they are interpreted and analyzed with movements and challenges as analytical and descriptive method.